Murphy Pizza, Paganistan: Contemporary Community in Minnesota’s Twin Cities - Charbonneau, Marisol (The pomegranate, 2022)
Murphy Pizza, Paganistan: Contemporary Community in Minnesota’s Twin Cities (Burlington, Vt.: Ashgate Publishing, 2014), 150 pp., $99.95 (hardback)